1972
DOI: 10.1085/jgp.59.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Adenosine Triphosphatase of Limulus polyphemus Actomyosin by Tropomyosin

Abstract: Purified actin does not stimulate the adenosine triphosphatase (ATPase) activity of Limulus myosin greatly. The ATPase activity of such reconstituted preparations is only about one-fourth the ATPase of myofibrils or of natural actomyosin. Actin preparations containing tropomyosin, however, activate Limulus myosin fully. Both the tropomyosin and the actin preparations appear to be pure when tested by different techniques. Tropomyosin combines with actin but not with myosin and full activation is reached at a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…However, the same studies indicated that the strongly bound myosin also ''potentiated'' actin-activated myosin ATPase to higher-than-control values, but only when tropomyosin was present in the assays performed, and not when actin was free of tropomyosin. These results mimicked observations previously noted for some invertebrate preparations (28). Hence, the suggestion of a discrete, tropomyosin-dependent ''potentiated state'' of the thin filament emerged.…”
Section: Close Encounters With Early Literaturesupporting
confidence: 88%
“…However, the same studies indicated that the strongly bound myosin also ''potentiated'' actin-activated myosin ATPase to higher-than-control values, but only when tropomyosin was present in the assays performed, and not when actin was free of tropomyosin. These results mimicked observations previously noted for some invertebrate preparations (28). Hence, the suggestion of a discrete, tropomyosin-dependent ''potentiated state'' of the thin filament emerged.…”
Section: Close Encounters With Early Literaturesupporting
confidence: 88%
“…Phosphorylation of the 20 000-dalton light chain is essential for this effect to occur. Potentiation of actin-activated ATPase activity by tropomyosin has also been reported for rabbit skeletal muscle under conditions that favor rigor complexes (Bremel et al, 1972) and in Limulus striated myosin at high ATP concentrations where the rigor complexes were minimal (Lehman & Szent-Gyorgyi, 1972). A recent report by Sellers (1980) indicates that the actin-activated ATPase activity in Limulus myosin is dependent on myosin light-chain phosphorylation.…”
Section: Discussionmentioning
confidence: 76%
“…Fractions of 3 ml were collected and analyzed by SDS PAGE (21). Those fractions showing the tropomyosin A and B chains, and containing no higher molecularweight contaminants, were pooled and dialyzed against 5 mM Tris-HCl and 50 mM MgCl2, pH 8.0 (23).…”
Section: Methodsmentioning
confidence: 99%